(untitled) (Journal of Population and Development, 2024)
People are now concerned more about environmental issues and desire to buy eco-friendly products. As awareness of green products has expanded, a growing focus has been on green product consumption. Therefore, this study aims to determine the factors influencing consumer buying intention towards green products in Bangladesh. In this regard, we developed a research model with the concepts of environmental awareness, green product awareness, green product price, green promotion, and health concerns. We collected empirical data through an online survey of 313 respondents interested in green product consumption. The suggested relationships in the proposed model were examined using the structural equation model. The data was analyzed using SPSS 25.00 and Smart PLS 3.0. The results of this study show that environmental awareness, green product awareness, and health concerns significantly influence the attitude towards green products, which, in turn, influences green product buying intention. The findings also indicate that health concern is the most significant factor in predicting users’ attitudes towards green products. The findings suggest that this comprehensive model can improve green product purchase intention, boost sales, and influence this area favourably.